Sustainable Community Development as a Main Motive of Good Governance System and Ethical Presentation in a Developing Nation - Prabowo, Hadi; Rowa, Hyronimus; Rusfiana, Yudi (Journal of Ethnic and Cultural Studies, 2023)
Sustainable development has been given special attention worldwide regarding the environment and preservation of natural resources. However, sustainable community development remains a little-explored area, specifically concerning power-dominant economies and as an ethical representation of managing a country's law and order situations. Therefore, the current study aims to determine the influence of power disruptions, that is, human and governance factors, on sustainable community development directly and indirectly via an underlying mechanism of public sector performance. To achieve the study objectives, the study adopted a quantitative research methodology with a random sampling technique by surveying 720 citizens of Indonesia. A statistical data analysis using structural equation modeling in SmartPLS showed that power disruptions negatively impacted public sector performance, leading to underdeveloped communities. The results also showed that high levels of social connections between public sector employees and citizens mitigated the negative influence of power disruptions on public sector performance leading to the sustainable development of culture and community. The current study adds value to the government science literature by combining the critical issue of power disruptions and sustainable community development in a single consolidated framework that considers the ethics of governing a nation. The results will also help policymakers and project-executing agencies discourage power disruptions and find solutions to damages caused at the planning stages.